THE EFFECT OF MES GAMES ON STUDENTS’ SPEAKING SKILLS IN EFL CLASSROOM - Ade Rachma; Imam Fauzi; Ratu Dea Mada; Nurul Faiza; Jihan Zafira (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
This study aims to examine the effectiveness of using MES Games in improving students’ speaking skills in an English as a Foreign Language (EFL) context. A quasi-experimental design with a pre-test and post-test control group was employed. The participants consisted of 62 tenth-grade students from a public senior high school in Indonesia, divided into an experimental group and a control group. The experimental group received instruction integrated with MES Games, while the control group was taught using conventional methods. Data were collected through a speaking test adapted from IELTS speaking band descriptors, covering fluency and coherence, lexical resource, grammatical range and accuracy, and pronunciation. The data were analyzed using descriptive statistics, paired samples t-test, and independent samples t-test. The results revealed that both groups showed improvement; however, the experimental group demonstrated a significantly higher increase in speaking performance compared to the control group. The findings indicate that the integration of MES Games had a statistically significant and practically strong effect on students’ speaking skills. This improvement is attributed to the interactive, engaging, and low-anxiety learning environment provided by game-based activities, which encouraged students to actively produce language.This study concludes that MES Games can serve as an effective and accessible digital tool to enhance speaking skills in EFL classrooms. The findings also highlight the potential of non-immersive web-based games in facilitating meaningful language use and reducing affective barriers in language learning.